Continuity and Change: Fifty Years of the Journal/Revue. Issue 1 (11th April 2017) - White, Graham
Abstract: This article surveys the first five decades of the Journal/Revue, with particular emphasis on patterns of change and continuity. The article presents a quantitative analysis of the articles published in the Journal/Revue, looking at, among other things, the balance of articles published in English and in French, the proportion of articles authored by women, the location and institutional affiliation of authors and the subject matter of published articles. Significant continuities emerge from the data, such as the predominance of Canadian-based authors writing on aspects of Canadian politics and the dominance of authors from large research-intensive universities. Yet change is also evident, for example in the number of women publishing in the Journal/Revue and in the emergence of articles in subfields not found in the Journal/Revue's earlier days, most notably Aboriginal politics, gender and politics, and race and ethnicity. Résumé: Cet article retrace les cinq premières décennies de la RCSP (Journal/Revue), en portant une attention particulière à des tendances de changement et de continuité. Il présente une analyse quantitative des articles publiés dans la RCSP (Journal/Revue), en examinant, parmi d'autres éléments, la proportion des articles publiés en anglais et en français et de ceux qui portent la signature des femmes, la provenance et l'affiliation institutionnelle des auteurs ainsi que la matière traitée. Les données font apparaître des continuités significatives, notamment la prédominance d'auteurs canadiens qui écrivent sur des aspects de la politique canadienne et le nombre prépondérant des auteurs issues des grandes universités axées sur la recherche. Pourtant, le changement est également manifeste, par exemple dans le nombre de femmes publiant dans la RCSP (Journal/Revue) et dans l'émergence d'articles dans les sous-champs qui ne figuraient pas à ses débuts et tout particulièrement la politique autochtone, le genre et la politique et la race et l'ethnicité.